Angiotensin-converting enzyme defines matrikine-regulated inflammation and fibrosis - O'Reilly,PJ; Ding,Q; Akthar,S; Cai,G; Genschmer,KR; Patel,DF; Jackson,PL; Viera,L; Roda,M; Locy,ML; Bernstein,EA; Lloyd,CM; et al. (JCI INSIGHT, 2017)
The neutrophil chemoattractant proline-glycine-proline (PGP) is generated from collagen by matrix metalloproteinase-8/9 (MMP-8/9) and prolyl endopeptidase (PE), and it is concomitantly degraded by extracellular leukotriene A4 hydrolase (LTA4H) to limit neutrophilia. Components of cigarette smoke can acetylate PGP, yielding a species (AcPGP) that is resistant to LTA4H-mediated degradation and can, thus, support a sustained neutrophilia. In this study, we sought to elucidate if an antiinflammatory system existed to degrade AcPGP that is analogous to the PGP-LTA4H axis. We demonstrate that AcPGP is degraded through a previously unidentified action of the enzyme angiotensin-converting enzyme (ACE). Pulmonary ACE is elevated during episodes of acute inflammation, as a consequence of enhanced vascular permeability, to ensure the efficient degradation of AcPGP. Conversely, we suggest that this pathway is aberrant in chronic obstructive pulmonary disease (COPD) enabling the accumulation of AcPGP. Consequently, we identify a potentially novel protective role for AcPGP in limiting pulmonary fibrosis and suggest the pathogenic function attributed to ACE in idiopathic pulmonary fibrosis (IPF) to be a consequence of overzealous AcPGP degradation. Thus, AcPGP seemingly has very divergent roles: it is pathogenic in its capacity to drive neutrophilic inflammation and matrix degradation in the context of COPD, but it is protective in its capacity to limit fibrosis in IPF.